FUNGSI WARIA DALAM MASYARAKAT DI PEKANBARU - Marbun, Iska Putri Lailasari; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Transsexual or a person who emotionally and psychologically feels that they belong to the opposite sex or more often called pansy/drag queen is one of the minorities who often marginalized by the society. Bad view from the society make the difficult to transsexual get a decent job. Society has always viewed negatively to transsexual without see any positive side owned from transsexual. The society does not see that there are so many function of transsexual. The society considers that the existence of a transsexual breake the values and norms in society. The society should be aware that transsexual need social service from the society. Social servise will make them aware that they life is worth to living and transsexual can be confidently while living in society.Keywords : transsexual, function, society